Building a framework based on european quality standards for prevention and e-learning to evaluate online training courses in prevention - Henriques, S.; Broughton, N.; Teixeira, A.; Burkhart, G.; Miovský, M. (Aditktologie, 2019)
Prevention practitioners are required to develop their skills and competencies in response to recent advances in prevention science. It is thus important to develop training programmes which ensure the development of a prevention workforce. Aiming to respond to this need, the Specialised Training Course in Addictions Prevention is based on the European Universal Prevention Curriculum (EUPC) and delivered online. In view of this being the first online course based on the EUPC, the absence of training programmes for prevention practitioners in Portugal, and the significance of international guidelines in these two domains (prevention and online distance learning), it was considered important to create a framework which supports the evaluation and monitoring of the course. This paper presents a framework for the evaluation of the specialised training course in prevention based on two models: the European Drug Prevention Quality Standards, and the adaptation of the European Standards and Guidelines to digital programmes and courses – Considerations for Quality Assurance of E-learning Provision. Given the importance of quality assurance in contemporary society, the framework presented in this paper is a tool that may be useful for evaluating other online distance learning programmes which focus on the professional development of prevention practitioners.